PEREMPUAN PELESTARI DAS, PEREMPUAN BERDA (Merintis Keberdayaan Pelajar Melakukan Pemberdayaan Perempuan Bersendikan Kearifan Lokal Sesuai Kurikulum 2013) - Fritz Hotman S. Damanik (Environmental Research Center (PPLH) of Udayana University, 2014)
In Indonesia, there are 5.590 main rivers, 65.017 tributaries, and 500 lakes (Status LingkunganHidup Indonesia, 2010). Ironically, the rivers’ surroundings and watershed have facedenormous pressure since years ago because of they became the center of the development ofcivilization as well as the center of communities’ social-economic activities. Furthermore, theanalysis to 40 watersheds in West Java indicated the decline of hydrological functions. 14watersheds can be categorized as extremely critical, while 8 watersheds considered to becritical. The same situations are believed to occur all across Indonesia.The Basic Competence of Sociology for Social Sciences Specialization in High School,contained the demand for students to able to design, implement, and report communitydevelopment action by using local wisdoms as foundation in the globalization era. From thisbasic competence, it is so appropriate to try to formulate an empowerment action for womenas watershed conservationist, with high scholl students as facilitators. Why womesn ? Theanswers mostly related to gender stereotypes associated to women, such as gentle, sensitive,patient, and full of considerations. The stereotypes will enable women to conservate as wellas using the environment continuously. Or by other words, women are assumed to have theability to improve welfare without ruin nature.